SYSTEM ANALYSIS OF MULTICRITERION OPTIMIZATION PROBLEM FOR INFORMATION SYSTEM PROTECTION (HACKING) - Коваленко, Юлія Борисівна (Ukrainian Information Security Research Journal, 2015)
The article discusses the solution of the system analysis multicriterion optimization problem and application of organizational and analytical methods development,justification and decision-making for solving the problemof choosing the means of fuzzing using genetic algorithms.Mathematical methods of analysis of expertassessments, method of analysis of hierarchies and themethod of paired comparisons are applied. A systematicanalysis of the fuzzing system using genetic algorithms,the search for the sources of the corresponding typesystem, compiling a comparative table of the prototypewith known systems of this type, a systematic analysis ofthe problems of multicriteria selection, expert evaluationof the advantages and construction of the matrices ofthe advantages of using the method of pairwise comparisons,the calculated vector of global priorities and decisionon the basis of the results of the analysis arerepresented in the article.